Perancangan Ulang Tata Letak Pada Toko Ritel Mitra Hotel - Nadira Salwa Faizaty; Bulan Wiranata Septiani; Akhdan Hadi Zahran; Fitriyani Fitriyani; Adam De Alvaroziq (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Mitra Hotel Retail Store is one of the retail stores engaged in selling various daily necessities. Based on the results of the initial survey, the layout at the Lodaya Branch Hotel Partner Retail Store is considered less effective because it has minimal capacity, causing long queues at the cashier and difficulty accessing certain shelves. This research aims to redesign the layout of the retail store to be more efficient and improve customer convenience. The method used is Entity Relationship Chart (ERC) analysis to determine the relationship between areas and Total Closeness Rating (TCR) to determine the priority of area proximity. The results of the analysis produce a new solution layout with area rearrangement based on proximity values. It is expected that with a better layout design, it will improve store operational performance and provide a pleasant shopping experience for customers.